2021
DOI: 10.3389/fonc.2021.736104
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Comparative Analysis of KRAS G12C vs. Other KRAS Mutations in mCRC Patients Treated With First-Line Chemotherapy Doublet + Bevacizumab

Abstract: BackgroundKRAS mutations in metastatic colorectal cancer (mCRC) define a subset of tumors that have primary resistance to anti-EGFR-based therapy. Data concerning whether different KRAS mutations may also have a prognostic value are lacking. Furthermore, novel KRAS G12C inhibitors are currently in development. The aim of our analysis was to compare response rates in patients treated with first-line chemotherapy doublet + Bevacizumab among different KRAS variants. Secondary end-points were progression free surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 23 publications
3
13
0
Order By: Relevance
“… 7 , 8 The presence of KRASG12C is rare (2%-4%), however, and so far, merely few and heterogenous retrospective series have evaluated the impact of KRASG12C on the response to chemotherapy and as a prognostic biomarker, with discordant results. 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 KRASG12C tumors were associated with a shorter OS compared with non- KRASG12C tumors. 9 , 10 , 11 , 12 , 13 Other studies reported that KRASG12C mutation conferred resistance with reduced overall response rate (ORR) to first-line chemotherapy doublets plus bevacizumab compared with different KRAS mutations, but did not affect progression-free survival (PFS) or OS.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“… 7 , 8 The presence of KRASG12C is rare (2%-4%), however, and so far, merely few and heterogenous retrospective series have evaluated the impact of KRASG12C on the response to chemotherapy and as a prognostic biomarker, with discordant results. 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 KRASG12C tumors were associated with a shorter OS compared with non- KRASG12C tumors. 9 , 10 , 11 , 12 , 13 Other studies reported that KRASG12C mutation conferred resistance with reduced overall response rate (ORR) to first-line chemotherapy doublets plus bevacizumab compared with different KRAS mutations, but did not affect progression-free survival (PFS) or OS.…”
Section: Introductionmentioning
confidence: 89%
“… 9 , 10 , 11 , 12 , 13 Other studies reported that KRASG12C mutation conferred resistance with reduced overall response rate (ORR) to first-line chemotherapy doublets plus bevacizumab compared with different KRAS mutations, but did not affect progression-free survival (PFS) or OS. 14 Finally, another study reported no difference in terms of response and OS across KRASG12C and other KRAS -mutant mCRC. 15 Furthermore, due to the retrospective nature of those studies, the small number of patients included in the studies and the setting and/or the type of chemotherapy regimens (mono-chemotherapy versus chemotherapy doublets, post-operative chemotherapy versus palliative treatment), the best treatment strategy is still unknown.…”
Section: Introductionmentioning
confidence: 98%
“…The importance of different KRAS mutations on the clinical behavior of metastatic CRC (mCRC) has been explored, and differences have been reported (9). The clinical relevance of KRAS-G12C is unclear (10)(11)(12)(13)(14)(15)(16)(17). The frequency of KRAS-G12C has been reported to be 2%-8% in large databases of molecularly analyzed CRCs (12,14,18,19).…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of KRAS-G12C has been reported to be 2%-8% in large databases of molecularly analyzed CRCs (12,14,18,19). In hospital-based series, the proportion of KRAS-G12C tumors was 2%-4% of all mCRC tumors (11,15,16,20), whereas greater variability was seen in the proportion of the KRAS-mutated population (6%-17%) (11,13,16,17,(20)(21)(22). Sex-and age-related differences and differences in the metastatic pattern have been reported between different KRAS mutations, with no consistent results (12,13,22).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation